SIFAT-SIFAT MEKANIK KOMPOSIT POLIPROPILENA BERPENGISI ABU PEMBAKARAN BIOMASSA KELAPA SAWIT - Danil Tarmizi, Kartini Noor Hafni, A. Haris Simamora (Universitas Sumatera Utara, 2014)
This study aimed to determine the effect of palm oil fuel ash composition of the mechanical properties of polypropylene composites. Composites made by extrusion and injection molding method by mixing polypropylene and palm oil fuel ash with filler composition, respectively 10, 15, and 20 (% w/w). Mechanical properties which tested are tensile strength, elongation at break, and impact strength. The results obtained from the study is the addition of filler palm oil fuel ash in polypropylene composites decrease the mechanical properties of the composites, such as tensile strength, elongation at break, and impact strength.